Evaluation of Horses' Daytime Activity Budget in a Model of Ethological Stable: A Case Study in Italy. Issue 2 (3rd April 2021) - Marliani, Giovanna; Sprocatti, Ilaria; Schiavoni, Giulia; Bellodi, Andrea; Accorsi, Pier Attilio
ABSTRACT: The increasing interest in animal welfare and the knowledge of equine physiological and ethological needs have led to the development of different types of horses' management and housing systems. The research presented here aimed to assess the daytime activity budget of horses. Focal animal sampling was used as an observational sampling method, and the five animals were observed for a total of 9920 minutes in the paddock and inside the stall. The results showed that horses spent most of the daytime in foraging behaviors, followed by resting behaviors, and locomotion. Social behaviors (s.e. allogrooming, olfactory investigation) were rare, and the stereotypic behaviors (s.e. oral and locomotor stereotypies) occupied 2.74%±2.74% of the total time. The percentage of time spent in foraging, resting, and locomotion, reflects the activity budget observed in free-roaming feral horses. However, the rare occurrence of positive social interactions and the presence of some stereotypies could be aspects to ameliorate. This kind of housing facility could be considered a good alternative to traditional management; indeed, it might offer a better trade-off between the needs of the horse and the management goals from humans.